1993
DOI: 10.1017/s0952523800003199
|View full text |Cite
|
Sign up to set email alerts
|

Visual processing in pigeon nucleus rotundus: Luminance, color, motion, and looming subdivisions

Abstract: The responses of single cells to luminance, color and computer-generated spots, bars, kinematograms, and motion-in-depth stimuli were studied in the nucleus rotundus of pigeons. Systematic electrode penetrations revealed that there are several functionally distinct subdivisions within rotundus where six classes of visual-selective cells cluster. Cells in the dorsal-posterior zone of the nucleus respond selectively to motion in depth (i.e. an expanding or contracting figure in the visual field). Most cells reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
166
5
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(182 citation statements)
references
References 25 publications
(36 reference statements)
10
166
5
1
Order By: Relevance
“…Wang et al (1993) found that neurons in the posterior nRT are motion sensitive, whereas neurons responsive to color and luminance are found in the anterior nRT. Husband and Shimizu (1999) showed that the caudal Ec receives input from the posterior nRT, and the rostral Ec receives input from the anterior nRT (Benowitz and Karten, 1976;Laverghetta and Shimizu, 2003).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Wang et al (1993) found that neurons in the posterior nRT are motion sensitive, whereas neurons responsive to color and luminance are found in the anterior nRT. Husband and Shimizu (1999) showed that the caudal Ec receives input from the posterior nRT, and the rostral Ec receives input from the anterior nRT (Benowitz and Karten, 1976;Laverghetta and Shimizu, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Four groups of neurons were found: color, luminance, simple motion, and looming (Sun and Frost, 1998). The color and luminance cells were found in the rostral areas of nRT, whereas the motion and looming cells were found in the caudal nRT (Wang et al, 1993).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, the eagle function (Reymond and Wolfe, 1981) and the kestrel function (Hirsch, 1982) are each comprised of data from a single subject only. This paucity of data is rather surprising considering the substantial literature that exists on the optics, anatomy, physiology, and histochemistry of the eye, the retina, and the central visual system of birds (Karten, 1969;Karten et al, 1973;Shimizu, Cox, and Karten, 1995;Hodos and Erichsen, 1990;Holden, 1980;Bagnoli, 1984;Wang, Jiang, and Frost, 1993), including a number of studies that have been carried out on their visual acuity (Hodos and Leibowitz, 1976;Hodos, et al, 1991a;Gaffney and Hodos, 2003;Güntürkün and Hahmann, 1994;Hahmann and Güntürkün, 1993;Schmid and Wildsoet, 1998;Porciatti, et al, 1991;Hirsch, 1982;Reymond and Wolfe, 1981;Reymond, 1987;Martin and Gordon, 1974;Fite, 1973;Fite and RosenfieldWessels, 1975;Fox, et al, 1976;Dabrowska, 1975;Blough, 1971; Orders combined. Since a great deal of diversity is found in avian visual morphology, specialized for various econiches, it would not be surprising to find avian species that had contrast sensitivities currently considered to be in the mammalian range.…”
Section: Research Objectivementioning
confidence: 99%